Innovative Teaching Technologies as a Way to Increase Students’ Competitiveness - Galynska, Olena; Shkoliar, N.; Dziubata, Z.; Kravets, S.; Levchyk, N. (My University, 2021)
The article presents an analysis of innovative teaching technologies as a way to increase students’ competitiveness. The author found that innovative technologies in education are information and communication technologies relying on computer-based learning. The structure, content of educational software, organization of Web-space are important when using innovative teaching technologies in English classes.
Keywords: teaching technologies; IT specialist; business game; case study technology; кафедра іноземних мов професійного спрямування; технології навчання; викладання англійської мови; ділові ігри